Aberrant subclavian artery origin in tetralogy of Fallot with pulmonary stenosis is associated with chromosomal or genetic abnormality. (4th June 2013) - Oswal, Nilesh; Christov, Georgi; Sridharan, Shankar; Khambadkone, Sachin; Bull, Catherine; Sullivan, Ian
Abstract We determined the relationship between aortic arch anatomy in tetralogy of Fallot with pulmonary stenosis and chromosomal or genetic abnormality, by performing analysis of 257 consecutive patients undergoing surgical repair from January, 2003 to March, 2011. Chromosomal or genetic abnormality was identified in 49 of the 257 (19%) patients. These included trisomy 21 (n = 14); chromosome 22q11.2 deletion (n = 16); other chromosomal abnormalities (n = 9); CHARGE (n = 2); Pierre Robin (n = 2); and Kabuki, Alagille, Holt–Oram, Kaufman McKusick, Goldenhar, and PHACE (n = 1 each). Aortic anatomy was classified as left arch with normal branching, right arch with mirror image branching, left arch with aberrant right subclavian artery, or right arch with aberrant left subclavian artery. Associated syndromes occurred in 33 of 203 (16%) patients with left arch and normal branching (odds ratio 1); three of 36 (8%) patients with right arch and mirror image branching (odds ratio 0.4, 95% confidence interval 0.1–1.6); seven of eight (88%) patients with left arch and aberrant right subclavian artery (odds ratio 36, 95% confidence interval 4–302); and six of 10 (60%) patients with right arch and aberrant left subclavian artery (odds ratio 8, 95% confidence interval 2–26). Syndromes were present in 13 of 18 (72%) patients with either right or left aberrant subclavian artery (odds ratio 15, 95% confidence interval 4–45). Syndromes in patients with an aberrant subclavian artery included trisomy 21 (n = 4); chromosome 22q11.2 deletion (n = 5); and Holt–Oram, PHACE, CHARGE, and chromosome 18p deletion (n = 1 each). Aberrant right or left subclavian artery in tetralogy of Fallot with pulmonary stenosis is associated with an increased incidence of chromosomal or genetic abnormality, whereas right aortic arch with mirror image branching is not. The assessment of aortic arch anatomy at prenatal diagnosis can assist counselling.